The knowledge and practices of mercury coated bulbs disposal among households at ga-Mokgwathi village, Limpopo Province, South Africa - Mokhasi, Lucky (University of Limpopo, 2014)
The purpose of this study was to investigate the knowledge and practices among households at Ga-Mokgwathi Village regarding the disposal of mercury coated bulbs. Cross-sectional design with quantitative approach was used in this study. The study objectives were to determine the knowledge about the disposal methods of mercury coated bulbs and also to determine the practices of handling broken mercury coated bulbs among the villagers of Ga-Mokgwathi. Data collection was done using self-administered questionnaires. Cluster random sampling was used in the study where a total number of 338 households were randomly selected to participate in the study. The results indicated that 36.7 % of the households at Ga-Mokgwathi Village had knowledge of safe disposal methods of mercury coated bulbs, 7.7% were not sure and 55.6% did not have such knowledge. Furthermore, the results indicated that 51.5% of the households had improper practices regarding the handling of broken mercury coated bulbs, 6.2% were not sure and 42.3% had proper practices regarding the handling of broken mercury coated bulb. The results of the study concluded that the majority of people were lacking knowledge of proper disposal methods and the handling of mercury coated bulbs. These results necessitate education of people about the disposal methods and handling of mercury coated bulbs.
Thesis ( MPH.) --University of Limpopo, 2014
Keywords: Waste Disposal; Mercury coated bulbs; Waste products; Public health -- Research; Health risk assessment